Economic and biological assessment of Tartary buckwheat variety ‘Kalyna’ - Л. А. Вільчинська; Т. М. Хоменко; О. В. Ночвіна (Plant Varieties Studying and Protection)
Purpose. To evaluate Tartary buckwheat variety ‘Kalyna’ according to morphological, productive and quality indicators in the conditions of the Research Center “State Agrarian and Engineering University in Podilia”. Methods. The studies were carried out in the field crop rotation of the Research Center “Podillia” of the State Agrarian and Engineering University in Podilia (SAEU) in 2015–2020. The soil cover of the experimental field is represented mainly by low-humus, weakly leached soils. Experiment setting, material evaluation, analysis of plants, yield and grain quality were carried out in accordance with the generally accepted methods of state variety testing. An assessment of the Tartary buckwheat variety ‘Kalyna’ was carried out in comparison with the common buckwheat variety ‘Victoriia’. Results. The growing season duration of Tartary buckwheat variety ‘Kalyna’ was 87 days (38 days vegetative and 49 days generative). In the studied variety, a larger number of the 1st order branches up to 5.5 pcs was observed. The number of leaves on the plant was 22–28 pcs./plants. In the studied variety, more than 50% of the grains were located on the main stem and the first order branches, while in common buckwheat this indicator was only 30%. Productivity was 2,28 t/ha, the number of grains in inflorescences was 4,4 grains, in common buckwheat – 0,72 t/ha, and 2.2 grains/inflorescence, respectively. The thousand kernel weight in Tartary buckwheat variety ‘Kalyna’ is 10.2 g less than in common buckwheat variety ‘Victoriia’ and is 17.4 g, with hulls – 19.5%, which is 3.2% less then in common buckwheat variety.Assessment of Tartary buckwheat variety ‘Kalyna’ for resistance to the effects of bio- and abiotic factors indicates that it was at the level of common buckwheat variety ‘Victoriia’.In terms of resistance to abiotic factors, ‘Kalyna’ variety is characterized by high resistance to spontaneous fallof grain (5 scores) and has simultaneous grain ripening (5 scores). Conclusions.The morphological and economic-biological indicators of Tartary buckwheat variety ‘Kalyna’ are significantly higher than the common buckwheat variety ‘Victoriia’. It is recommended to grow Tartary buckwheat variety ‘Kalyna’ as a valuable cereal crop in the Western Forest-Steppe zone.